Making a Mobile-Based Social Media Information System for Environmentalists with Flutter and AWS - Mohamad Alvin Renaldi; Riyo Putra Syam Satria; Nanda Octavia; Muhammad Danang Mukti Darmawan; Ivan De Nerol; Firdayanti; Fiqri Nurfadillah; Fiona Kharismatunnisaa; Ester Angeline; Yourdan Saputra (Journal of Applied Science, Technology & Humanities | JASTH, 2024)
This research explores an effective role in environmental conservation through technological innovation. This study aims to design and develop a mobile-based social media application by utilizing Flutter technology and AWS architecture. The research focuses on managing user data securely and efficiently through AWS services. This research uses an applied method based on the Scrum framework, emphasizing technology integration for environmental preservation and AWS implementation for data security. The results showed successful application development in line with the company's environmental sustainability mission. The data management system ensures safe and efficient handling of user information. The study concludes with a summary of findings, emphasizing the positive impact of technology on environmental initiatives.